HISTORIOGRAPHY & MYTHOLOGY OF BENGAWAN SALA - Sumardjoko, Bambang (Prodi. Pendidikan Sejarah FPIPS UPI dan APPS (Asosiasi peneliti dan Pendidik Sejarah), 2010)
The aims of this research are: [1]. Describing the historiographic dimension of Bengawan Sala (Solo River), [2]. Describing the mythology alive in the peopleâ€™s mind along the River Sala, [3]. Formulating revitalization of historiography and mythology of Bengawan Sala which can support the development of tourism in Surakarta. This is a qualitative research making use of primary and secondary sources. Research data were collected by using in-depth interviews, guided group discussions, field observations, and a close reading method (metode simak). Triangulation of data sources was done to ensure the validity of data. Data were analyzed by using the technique of interactive model. The results of the research show that [1]. Historiography of Bengawan Sala is important and singularly valuable when it is viewed from its historical perspective. From its historiographic aspect, Bengawan Sala was a main and urgent channel of transportation before the coming of train, cars and airplanes. [2]. The meanings of mythology around Bengawan Sala, such as Kerek, Lubuk Maya, Bengawan Goa Sentana, Benawi Getas, Lubuk Werpitu, all show the â€œsacrednessâ€ [or â€œkeangkeranâ€] of Bengawan Sala as a channel for transportation. This mythological story functions to remind all boating people through such areas to be careful because those areas are the place where two different streams from the opposite direction meet each other, or where whirl pools happen. Mythological story of Tinggang depicts the giants which already died, â€œambreganggangâ€ shortened as â€œTinggang.â€ People believe that the big wood fossils scattered in the area are the bones of the giants which were already dead, â€œambreganggangâ€œ [or â€œfell down criss-crossingâ€]. That mythology shows that the lands around Bengawan Sala are fertile. [3]. The exploratory research gives a basic model of â€œRevitalization Based on the Historiography of Bengawan Salaâ€ (or â€œRevitalisasi Bengawan Sala Berbasis Kesadaran Sejarahâ€), that is revitalization of Bengawan Sala through the historiography and mythology development of it.